Contribution of Daily General Mobility to PM10 Concentration Development in Sisak-Moslavina County, Croatia during the Covid-19 Pandemic in 2020 - Teodor B. Iliev; Tea Sikirica; Darko Špoljar; Renato Filjar (Communications - Scientific letters of the University of Zilina, 2022)
Carbon and pollutant emissions drive climate change and affect health and daily life. The Covid-19 pandemic created an unprecedented opportunity to understanding the impact of carbon and pollutant emission. In this paper were identified Telecommunications records-derived general mobility indices as contributors to the PM10 pollutant concentration development in industry-intensive Sisak-Moslavina County, Croatia, during the Covid-19 outbreak in 2020. Time-series of daily mean PM10 concentrations and mobility changes indicators are analysed for their statistical properties identification, decomposed, and the decomposing components examined for association using Tailored software developed in the R environment for statistical computing.